2014
DOI: 10.1002/lary.24817
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Clavien-Dindo classification system for complications in head and neck surgery

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 14 publications
0
62
0
Order By: Relevance
“…Clavien-Dindo Classification Score I complications were seen in six patients and were without exceptions secondary bleedings [11]. A light secondary bleeding according to a grade A-C described by Sarny et al in 2011 was observed in five patients, which was effectively treated with electro cautery or conservative therapy [13].…”
Section: Surgical Complicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Clavien-Dindo Classification Score I complications were seen in six patients and were without exceptions secondary bleedings [11]. A light secondary bleeding according to a grade A-C described by Sarny et al in 2011 was observed in five patients, which was effectively treated with electro cautery or conservative therapy [13].…”
Section: Surgical Complicationsmentioning
confidence: 90%
“…In random laterality, the tonsillar pillars were approximated on one side with an interrupted suture and on the opposite side with a running suture. Outcome parameters were incidence of suture dehiscence within an observation period of 21 days postoperatively, time needed to perform the suture in minutes and incidence of postoperative complications according to the Clavien-Dindo classification [11].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies broadly define complications as medical or surgical. 11 We also graded complications according to the Clavien-Dindo classification, independently validated in head and neck surgical cases, 22 so that complications could be evaluated based on the severity of their intervention according to a predefined scale. Clark et al and Patel et al defined a major medical or surgical complication as any adverse event requiring intervention or affecting length of stay.…”
Section: Evaluating Postoperative Complicationsmentioning
confidence: 99%
“…What makes our study unique is that our definition of the postoperative complication is derived from previous work where all postoperative events for a similar patient cohort were first collected and then analyzed to determine which events could be discriminated from the expected postoperative course and also accurately recorded between patients. 11 We also graded complications according to the Clavien-Dindo classification, independently validated in head and neck surgical cases, 22 so that complications could be evaluated based on the severity of their intervention according to a predefined scale.…”
Section: Evaluating Postoperative Complicationsmentioning
confidence: 99%
“…1–3 One study has assessed whether the CD classification is suitable for classifying complications after head and neck reconstruction, whereas another has identified the factors that lead to major (CD grade III–V) complications. 4,5 However, little has been published about the efficacy of the CD classification in larynx-preserving esophageal reconstruction.…”
mentioning
confidence: 99%